Lattice physics calculations using the embedded self-shielding method in Polaris, Part I: Methods and implementation. (January 2021) - Jessee, Matthew A.; Wieselquist, William A.; Mertyurek, Ugur; Kim, Kang Seog; Evans, Thomas M.; Hamilton, Steven P.; Gentry, Cole
Highlights: Polaris provides accurate light water lattice physics analysis with ESSM. The accuracy of ESSM depends on the multigroup library generation procedure. ESSM is applicable to wide range of problems with consistent library generation. Abstract: Polaris is a 2-dimensional multigroup lattice physics capability in the SCALE code system for the analysis of light water reactor fuel designs. The goal of light water reactor lattice physics codes is to generate few-group homogenized cross sections for downstream full-core nodal diffusion calculations. Lattice physics calculations contain three primary components: the cross section processing calculation, the 2D transport calculation, and the depletion calculation. This paper summarizes the calculational methods and their implementation into Polaris, with an emphasis on implementation of the embedded self-shielding method. The accuracy of the embedded self-shielding method depends on the procedure used to generate self-shielding factors on the multigroup library. Numerical benchmarks calculations reveal that the accuracy of Polaris eigenvalue predictions is enhanced by (1) using heterogeneous unit cell models to generate the self-shielding factors on the library and (2) using self-shielding factors for within-group scattering cross section.